Analisis Faktor Faktor Yang Berpengaruh Terhadap Kenaikan Pangkat Pegawai Pada Balai Wilayah Sungai Sulawesi IV (BWS,SIV) Provinsi Sulawesi Tenggara - Nartin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This research executed in body of officer area of town Kendari with the amount of population and sample as much 62 people by using descriptive analyisi model which is good for obtaining variable picture trussed by effectiveness management of free increase rank and variable of officer interest ,system and procedure and also this policy target head research is (1) Analyzing factor influencing effectiveness of management of promotion PNS at Regional Hall of river of Sulawesi IV (BWS,S IV) Provensi south east Sulawesi,(2) Descriptive of Effectiveness of management of Promotion PNS AT Regional hall of River of Sulawesi IV (BWS,S IV) Provensi south east Sulawesi. This research test the factors having an effect on to effectiveness of promotion management in regional hall of river of Sulawesi IV (BWS,S IV) Provensi south east Sulawesi With the average value give the influence significant . that way also coefficient regression (B) For the variable of officer interest (X1), Of head policy (X3), Give the influence siknificant,of while variable of system and procedure (X2), Have and effect not siknificant. From the examination result of factor of head policy refresent the dominant factor have an in with the effectiveness of promotion management at Regional hall of River of Sulawesi IV (BWS, SIV) Provensi South east Sulawesi, after performent by examination with the teast F and teast the showing of influence significant.